Menimbang Agresivitas Dalam Beragama Perspektif Komunikasi Lintas Agama - Iskandar, Amin; Mamin, Mamin (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2024)
Aggressive behavior (aggressiveness) often appears to trigger conflicts between religious communities. Conflicts that occur arise from verbal aggressiveness. The response to verbal aggressiveness which was then uncontrolled then increased to physical aggressiveness. This study was conducted through a literature review of several studies related to aggressive behavior. The purpose of this study is to find out how to reduce aggressive behavior in religious life. The results of a review of several studies can be concluded that one of the effective ways to reduce aggressive behavior is to carry out inter-religious dialogue and provide punishment (negative consequences). This study also provides an illustration of the importance of cleaning up the image of religion from hostility, disputes and disputes which lead to conflicts between religious adherents which must be resolved by good interfaith communication. Keyword: aggressiveness; religious conflict; communication